Surface crystallographic structure insensitive growth of oriented graphene domains on Cu substrates. (June 2020) - Hou, Yuting; Wang, Bojun; Zhan, Longlong; Qing, Fangzhu; Wang, Xiaomu; Niu, Xiaobin; Li, Xuesong
Graphical abstract: Abstract: Cu-based chemical vapor deposition method can produce large-area graphene films, usually polycrystalline films with grain boundaries as the main defects. One way to reduce grain boundaries is to grow oriented graphene domains (OGDs), which can ultimately perfectly integrate. In contrast to previously reported methods of limiting OGD growth on Cu (1 1 1), we find that OGDs can grow on Cu substrates with a large surface crystallographic structure tolerance. Density functional theory calculations show that this is due to the single lowest energy state of graphene nucleation. The growth temperature is crucial. It must be high enough (1045 °C) to suppress mis-OGD nucleation, but not too high (1055 °C) to deteriorate OGD growth. Mis-OGD nucleation can also be caused by C impurity in Cu grains, which can be depleted by thermal pretreatment of the substrate in an oxidizing atmosphere. On the other hand, OGD growth is not sensitive to the atmosphere at growth stage within the range that we have tested.